Revisiting the Concept of Social Exclusion: It’s Relevance to Policies against Poverty in Latin America - Leyton Navarro, Cristian; Muñoz Arce, Gianinna (Revista del CLAD Reforma y Democracia, 2016)
The notion of social exclusion emerged in France in the 1960s and took great relevance to welfare policies promoted by the European Union in the early 1990s. Later on, such a concept was employed in Latin America through the works produced by the International Labour Organization (ILO) mainly. Despite the concept of social exclusion is still mentioned in policies against poverty delivered within the Latin American context, its relevance has diluted during the last decade. Poverty, along with vulnerability, risk and social protection, have become dominant concepts in this field. Drawing upon the proposals of Peter Townsend (1979 and 1997), John Veit-Wilson (1998) and Ruth Levitas (2005 and 2013), this article aims to revisit the critical approach of social exclusion, a perspective which is not only relevant but urgent to be included in policies against poverty in Latin America. Four characteristics of the Latin American context are identified in order to justify the need of such an approach: i) the colonial trauma and the monopolization of channels of influence, ii) the fragility of welfare systems and the limited coverage of rights; iii) the deficits of citizenship and the weakness of democratic systems, and iv) the inequality gaps.